2017
DOI: 10.1142/s0217590816500429
|View full text |Cite
|
Sign up to set email alerts
|

The Capital Flight From India: A Case of Missing Woods for Trees?

Abstract: The surge of capital inflow into emerging markets since the 1990s has attracted much research, but capital flight from these economies has received scant attention in research and policy debates, despite its severe implications. The present study attempts to address the issue of capital flight and gap in the literature. Our estimates show a steep increase in the magnitude of capital flight from India since 2003, and empirical results suggest that the significant determinants of capital flight are GDP and excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
3
15
1
Order By: Relevance
“…The findings were consistent with findings by Domfeh et al (2018) and Uddin, Yousuf and Islam (2017 who reported that GDP had no significant relationship with capital flight. The findings however were inconsistent with several studies carried out by Forson et al (2017) and Bekele (2017) who reported a negative association and Salandy and Henry (2018) and Pradhan and Gourishankar (2017) who reported a positive relationship.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…The findings were consistent with findings by Domfeh et al (2018) and Uddin, Yousuf and Islam (2017 who reported that GDP had no significant relationship with capital flight. The findings however were inconsistent with several studies carried out by Forson et al (2017) and Bekele (2017) who reported a negative association and Salandy and Henry (2018) and Pradhan and Gourishankar (2017) who reported a positive relationship.…”
Section: Resultscontrasting
confidence: 77%
“…The findings were consistent the theory of Capital flight. The findings were consistent with findings by Pradhan and Gourishankar (2017); Cheung et al (2016) and Ahmad and Sahto (2016) but inconsistent with study by Egbe (2015) whose results showed that capital flight and real exchange rate had no significant relationship.…”
Section: Resultssupporting
confidence: 54%
“…It is worthwhile to clarify the concept of capital flight in relation to capital flows as well as distinguish capital flight from the capital flight trap. Consistent with Pradhan and Hiremath (2017), there is no consensus on the definition of capital flight because scholars are divided on the method by which it is estimated. According to Kindleberger (1987), capital flight represents "abnormal capital flows" given that these underlying outflows are traceable to suspicion and fears about future economic outlook.…”
Section: Introductionmentioning
confidence: 99%
“…Another stream of authors links capital flight to illegality or illegal income sources (Reuter & Truman, 2004;Perez et al, 2012). Capital flight can also be acknowledged as some of portfolio diversification in a strategy of hedging against macroeconomic risks and shocks (Eggerstedt et al, 1995;Collier et al, 2001;Hermes & Lensink, 2001;Buiter & Szegvari, 2002;Pradhan & Hiremath, 2017). As documented by Pradhan and Hiremath (2017), because capital flows are anticipated to move from developed to developing countries owing to higher marginal productivity of capital in the latter countries, it is reasonable to qualify the flow of capital from developing countries as "capital flight".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation